Survei Sarana dan Prasarana Pendidikan Jasmani di SMA, MA dan SMK - Saputro, Titus; Kurniawan, Ari Wibowo; Yudasmara, Dona Sandy (Sport Science and Health, 2020)
Abstract: This study aims to determine the availability of facilities and infrastructure for Sports and Health Physical Education in SMA, MA and SMK Negeri Kota Kediri. The subjects of this study were 8 schools and used random sampling techniques. Based on the results of the study, it can be concluded that for physical education and sports facilities, namely 7 schools for proper volleyball equipment, 6 schools for proper soccer equipment, 8 schools for proper gymnastics equipment, 8 schools for proper athletic equipment. Overall, it is said to be feasible and for Physical Education and Sports infrastructure, which is suitable for 2 schools and those that are less feasible, 6 schools of the total are said to be less feasible.Â Abstrak:Penelitian ini bertujuan untuk mengetahui ketersediaan sarana dan prasarana Pendidikan Jasmani Olahraga dan Kesehatan di SMA, MA dan SMK Negeri Kota Kediri. Subjek penelitian ini adalah 8 sekolah dan menggunakan teknik random sampling. Berdasarkan hasil penelitian dapat disimpulkan bahwa untuk sarana Pendidikan Jasmani dan Olahraga yaitu peralatan bolavoli yang layak sebanyak 7 sekolah, peralatan sepakbola yang layak sebanyak 6 sekolah, peralatan bolabasket yang layak 8 sekolah, peralatan senam yang layak 8 sekolah, peralatan atletik yang layak 8 sekolah dari keseluruhan dikatakan layak dan untuk prasarana Pendidikan Jasmani dan Olahraga yaitu yang layak 2 sekolah dan yang kurang layak 6 sekolah dari keseluruhan dikatakan kurang layak.